Strategi Komunikasi Kontekstual dalam Pengajaran Keterampilan Berbicara Bahasa Arab Pesantren Tradisional: Studi Kasus di Pondok Pesantren Mamba’us Sholihin Gresik - Haq, Muhammad A’inul; Makinuddin, Mohammad; Amrulloh, Friendis Syani (Journal of Arabic Language Studies and Teaching, 2025)
This study examines the implementation of contextualised communication strategies, grounded in Communicative Language Teaching (CLT), for teaching Arabic speaking in a Salafi pesantren, with a focus on Mamba’us Sholihin. Using a critical ethnographic case study, data were gathered through 120 hours of participant observation across classrooms, religious activities, and dormitories, as well as in-depth interviews with eight teachers and fifteen students, within its unique daily educational ecosystem. Findings show: (1) The pesantren’s CLT implementation entails complex negotiation with Salafi cultural values, integrating Arabic into religious practices, and relying on teachers and the kyais as essential socio-cultural mediators. (2) The hierarchical structure of the pesantren constrains open critical expression, necessitating cautious pedagogical adaptation. The study concludes that effective CLT in this context hinges on continual negotiation and adaptation to local values, and recommends developing a systematic, “glocalized” pedagogical framework that aligns CLT principles with the cultural and religious ethos of the Salafi Pesantren Mamba’us Sholihin.